2019
DOI: 10.14744/bej.2019.25338
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silicone Oil Endotamponade on Subfoveal Choroidal Thickness After Pars Plana Vitrectomy for Rhegmatogenous Retinal Detachment

Abstract: To evaluate the potential effects of 1000-cSt silicone oil (SO), which is used for pars plana vitrectomy (PPV) surgery on subfoveal choroidal thickness. Methods: In this retrospective study, 20 eyes of 20 patients who had undergone PPV and SO injection surgery for maculaoff rhegmatogenous retinal detachment were included. Complete ophthalmologic examinations were performed before the surgery, one month, three months after PPV and two months after silicone oil removal. After one month following PPV and SO injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…14 Mean sub-foveal choroidal thickness was significantly reduced following silicone oil tamponade and the choroidal thickness further decreased after silicone oil removal. 15 Similar results were generated in another study by Karimi et al which showed not just a decrease in choroidal thickness after silicone oil tamponade, but also a failure of the thinned out choroid to attain its preoperative thickness. 16 Interestingly, the degree of decrease in choroidal thickness was directly proportional to the duration of silicon oil tamponade.…”
Section: Resultssupporting
confidence: 80%
“…14 Mean sub-foveal choroidal thickness was significantly reduced following silicone oil tamponade and the choroidal thickness further decreased after silicone oil removal. 15 Similar results were generated in another study by Karimi et al which showed not just a decrease in choroidal thickness after silicone oil tamponade, but also a failure of the thinned out choroid to attain its preoperative thickness. 16 Interestingly, the degree of decrease in choroidal thickness was directly proportional to the duration of silicon oil tamponade.…”
Section: Resultssupporting
confidence: 80%
“…In this study, the mean BCVA before silicone oil removal was 0.75 LogMAR, but afterward, it improved to 0.69, 0.61, and 0.58 at 1, 4, and 8 weeks post SO removal, respectively. Similar results were found by Selim et al (2019), who assessed BCVA before and 8 weeks after removal; the BCVA was 0.05 dec and 0.05–0.8 dec, consecutively [ 29 ]. A study by Nassar et al (2019) also reported that 6 months or >6 months of SO application affected BCVA.…”
Section: Discussionsupporting
confidence: 84%
“…5 Furthermore, due to the potential adverse effects of silicone oil on the retina, gas use in appropriate cases emerges as an advantage factor. 10 The inventor of this surgical procedure, Tornambe, applied PR to 302 patients with RRD and achieved a success rate of 68% in a single surgical intervention and 95% with additional surgeries. 11 In a review conducted by Chan et al, the rate of PR efficacy in surgical success was found to be approximately 75%, ranging from 45% to 90%.…”
Section: Discussionmentioning
confidence: 99%